1993
DOI: 10.1172/jci116238
|View full text |Cite
|
Sign up to set email alerts
|

Neointimal macrophages colocalize with extracellular matrix gene expression in human atherosclerotic pulmonary arteries.

Abstract: Vascular remodeling in adult atherosclerotic pulmonary arteries is characterized by discrete areas of neointimal extracellular matrix gene expression, suggesting regulation by local factors. Though the factors responsible for inducing matrix gene expression in atherosclerotic lesions are largely unknown, several observations suggest macrophages may be a focal source of those factors.Immunohistochemistry confirmed the presence of macrophages in the neointima of atherosclerotic elastic pulmonary arteries from pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 37 publications
1
24
0
1
Order By: Relevance
“…For example, tropoelastin and type I procollagen are expressed by smooth muscle cells within a thick, fibrous neointima composed of smooth muscle-like cells, macrophages and extracellular matrix, similar to the atherosclerotic lesions found in systemic arteries (1)(2)(3)(4). In contrast to systemic arteries, however, neointimal or atherosclerotic changes are rarely observed in normotensive elastic pulmonary arteries, even in the elderly (1) or in the presence of risk factors for systemic vascular atherosclerosis such as diabetes, tobacco smoke, or hypercholesterolemia (2).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…For example, tropoelastin and type I procollagen are expressed by smooth muscle cells within a thick, fibrous neointima composed of smooth muscle-like cells, macrophages and extracellular matrix, similar to the atherosclerotic lesions found in systemic arteries (1)(2)(3)(4). In contrast to systemic arteries, however, neointimal or atherosclerotic changes are rarely observed in normotensive elastic pulmonary arteries, even in the elderly (1) or in the presence of risk factors for systemic vascular atherosclerosis such as diabetes, tobacco smoke, or hypercholesterolemia (2).…”
Section: Introductionmentioning
confidence: 90%
“…Immunohistochemistry was performed with antibodies to ␣ -smooth muscle actin (Sigma Chemical Co.), macrophages (HAM-56, DAKO), and angiotensin-converting enzyme as previously described (4,26,27).…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemical studies have revealed increased expression of TGF-β, matrix proteins (such as collagen, elastin, fibronectin, tenascin-C, and glycosaminoglycans) (17), macrophages, and T cells (18) as well as inflammatory mediators such as S100A4 (also known as metastasin 1 [Mts1]) (19) and fractalkine (20).…”
mentioning
confidence: 99%
“…30 Expression of NO is elevated in atherosclerotic lesions [31][32][33] as well as in the coronary arteries of human 19 and animal model 20,34 cardiac allografts. Although iNOS was originally identified in cytokine-activated macrophages, several reports have demonstrated that vascular SMCs in culture also produce iNOS [35][36][37][38][39][40] in response to TNF-␣ and IL-1␤. [35][36][37] NOdependent TNF-␣ induction of fibronectin expression was demonstrated in a human umbilical vein endothelial cell line.…”
mentioning
confidence: 99%